Novel Application of 18F-NaF PET/CT Imaging for Evaluation of Active Bone Remodeling in Diabetic Patients With Charcot Neuropathy: A Proof-of-Concept Report - Tram, Nguyen K.; Chou, Ting-Heng; Patel, Surina; Ettefagh, Laila N.; Go, Michael R.; Atway, Said A.; Stacy, Mitchel R. (Frontiers in Medicine, 2022)
Charcot neuropathic osteoarthropathy (CN) is a serious and potentially limb-threatening complication for patients with diabetes mellitus and peripheral arterial disease. In recent decades, nuclear medicine-based approaches have been used for non-invasive detection of CN; however, to date, a positron emission tomography (PET) radionuclide specifically focused on targeted imaging of active bone remodeling has not been explored or validated for patients with CN. The radionuclide 18F-sodium fluoride (NaF) has historically been used as a bone imaging probe due to its high sensitivity for targeting hydroxyapatite and bone turnover, but has not been applied in the context of CN. Therefore, the present study focused on novel application of 18F-NaF PET/computed tomography (CT) imaging to three clinical cases of CN to evaluate active bone remodeling at various time courses of CN. PET/CT imaging in all 3 cases demonstrated focal uptake of 18F-NaF in the bones of the feet afflicted with CN, with bone retention of 18F-NaF persisting for up to 5 years following surgical reconstruction of the foot in two cases. On a group level, 18F-NaF bone uptake in the CN foot was significantly higher compared to the healthy, non-CN foot (p = 0.039). 18F-NaF PET/CT imaging may provide a non-invasive tool for monitoring active bone remodeling in the setting of CN, thereby offering novel opportunities for tracking disease progression and improving treatment and surgical intervention.